Black Women, Academe, and the Tenure Process in the United States and the Caribbean - Esnard, Talia (Springer International Publishing, 2018)
This book explores the meanings, experiences, and challenges faced by Black women faculty that are either on the tenure track or have earned tenure. The authors advance the notion of comparative intersectionality to tease through the contextual peculiarities and commonalities that define their identities as Black women and their experiences with tenure and promotion across the two geographical spaces. By so doing, it works through a comparative treatment of existing social (in)equalities, educational (dis)parities, and (in)justices in the promotion and retention of Black women academics. Such interpretative examinations offer important insights into how Black women's subjugated knowledge and experiences continue to be suppressed within mainstream structures of power and how they are negotiated across contexts.